Understanding the Trauma of Menstrual Irregularity After COVID Vaccination: A Bird’s-Eye View of Female Immunology - Minakshi, Rinki; Rahman, Safikur; Ayaggari, Archana; Dutta, Durgashree; Shankar, Abhishek (Frontiers in Immunology, 2022)
The intricacies in various signaling routes involved in the menstrual cycle can be impacted by internal as well as external stimuli, and the role of stress, be it physical, psychological, or social, in disturbing the process could be debilitating for a woman. The global endeavor of vaccination rose to protect individuals from the severity of COVID-19, but a conjunction of a short-lived menace of menstrual disturbance in the female population came out as an unsettling side effect. An understanding of the immunological panorama in the female reproductive tract (FRT) becomes important to fathom this issue. The close-knit microenvironment in the FRT shows active microbiota in the lower FRT, but the latest findings are ascertaining the presence of low-biomass microbiota in the upper FRT as well. Concerted signaling, wherein inflammation becomes an underlying phenomenon, results when a stressor elicits molecules of the inflammatory cascade. Learning lessons from the gut microbiota, we need to address the exploration of how FRT microbiota would impose inflammation by manipulating the immune response to vaccines. Since there is a prominent sex bias in the immune response to infectious diseases in women and men, the role of sex hormones and cortisol becomes important. The treatment regimen may be considered differently in women who also consider their ovarian cycle phases. Women exert robust immune response to antigenic encounters via cell-mediated and humoral arms. The inclusion of women in vaccine trials has been marginalized over the years, which resulted in unwanted high dosage administration of vaccines in women.